Representaciones sociales e inclusión en mujeres transgénero de la ciudad de Ibagué (2023)
Although in the 1990s the formulation of policies in favor of the social inclusion of the LGBTI population (lesbian, gay, bisexual and transgender) had great and important developments, beyond the policies and regulatory frameworks, the practices of discrimination, discrimination, exclusion and violence against these sectors of the population persist today in the city of Ibagué and the transgender community, which is often one of the most targeted communities, exclusion and violence against these population sectors persist today in the city of Ibagué and the transgender community, which tends to be one of the most attacked communities, so this study aims to understand the social representations and inclusion in transgender women in the city of Ibagué.